Ethylenediaminetetraacetic Acid-Zn2+ System as Corrosion Inhibitor for Carbon Steel in Sea Water - Manivannan, M.; Rajendran, S. (Asian Journal of Chemistry, 2012)
The inhibition efficiency of ethylenediaminetetraacetic acid (EDTA) in controlling corrosion of carbon steel in sea water in absence and presence of Zn2+ has been evaluated by weight loss method. The formulation consisting of 250 ppm EDTA and 50 ppm Zn2+ has 96 % inhibition efficiency. It is found that the inhibition efficiency of EDTA increases by the addition of Zn2+ ion. A synergistic effect exists between EDTA and Zn2+. Polarization study reveals that EDTA-Zn2+ system functions as mixed inhibitor and the formulation controls the cathodic reaction predominantly. FTIR spectra reveal that the protective film consists of Fe2+-EDTA complex and Zn(OH)2. The surface morphology of the protective film on the metal surface was characterized by SEM study.